2020
DOI: 10.1176/appi.ajp.2019.19060654
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Cohort Study Examining the Incidence and Impact of Psychotic Experiences From Childhood to Adulthood, and Prediction of Psychotic Disorder

Abstract: Objective: To investigate the incidence, course and outcome of psychotic experiences from childhood through early adulthood in the general population, and prediction of psychotic disorder.Methods: A population-based cohort study using the semi-structured Psychosis-like Symptoms interview of psychotic experiences at ages 12, 18, and 24 (N=7900 with any data). Incidence rates were estimated using flexible parametric modelling, and positive predictive values (PPV), sensitivity, specificity, and area under the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
115
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 136 publications
(121 citation statements)
references
References 45 publications
4
115
0
2
Order By: Relevance
“…As prodromal symptoms mentioned in PQ-B were often mixed with psychotic-like experiences (PLEs) that commonly existed in the general population [49][50][51][52], subjects who only had PLEs may also been tested positive with PQ-B, causing false positives. Also, being rated in a clinical setting, rather than a non-clinical setting, may help the participants better understand the prodromal symptoms mentioned in the scale, and thus reducing false positive errors.…”
Section: Discussionmentioning
confidence: 99%
“…As prodromal symptoms mentioned in PQ-B were often mixed with psychotic-like experiences (PLEs) that commonly existed in the general population [49][50][51][52], subjects who only had PLEs may also been tested positive with PQ-B, causing false positives. Also, being rated in a clinical setting, rather than a non-clinical setting, may help the participants better understand the prodromal symptoms mentioned in the scale, and thus reducing false positive errors.…”
Section: Discussionmentioning
confidence: 99%
“…Sub-clinical hallucinatory and delusional experiences, commonly referred to as psychotic-like experiences (PEs), have recently been considered as one potential early indicator of mental health and functioning risk among children and adolescents (13)(14)(15). PEs themselves are not uncommon, particularly in childhood and adolescence (16), with up to 17% of 9-12-year-olds reporting hallucinatory or delusional phenomena (17). However, childhood and adolescent PEs are associated with both concurrent (15) and later psychopathology (16,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…PEs themselves are not uncommon, particularly in childhood and adolescence (16), with up to 17% of 9-12-year-olds reporting hallucinatory or delusional phenomena (17). However, childhood and adolescent PEs are associated with both concurrent (15) and later psychopathology (16,(18)(19)(20). Furthermore, recent evidence has demonstrated that adolescents who report PEs are at increased risk of compromised functioning, even when accounting for psychopathology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that, when experienced by youth, PEs may be clinicopathologically signi cant. They have been found to be associated with concurrent (4)(5)(6) and later psychopathology (1,(7)(8)(9), and with multi-morbidity (4).…”
mentioning
confidence: 99%